Generic Spherically Symmetric Thin-shells in General Relativity - Benghrian, Asma Ali Abdulsalam (Eastern Mediterranean University EMU, 2017)
We give a full investigation and assessment on the general spherically symmetric time-like thin shells in general relativity. In this main stream, we give the details of the Israel junction conditions which are used for gluing two distinct space-times on a hyper-surfaces including the case of time-like shells. We also study the general stability of thin-shells against a radial perturbation. Our results are fully analytic in closed forms. Keywords: Thin-shells, General relativity, Spherically symmetric, Stability, Israel junction conditions.

ӦZ: Küresel simetrik genel görelilikle zaman-benzer ince kabuklar üzerinde araştırma ve değerlendirme yaptık. Bu ana akımda ĺsrail sınır koşulları detaylarının göz önünde bulundurulduğunda bunlar iki farklı uzay-zaman benzeri kabuklar dahil olmak üzere yüzeylerin yapıştırılmasında kullanılır. Ayrıca ince kabukların radyal pertürbasyonlara karşı genel kararlılığını da inceledik. Sonuçlarımız kapalı formlarda tamamen analitiktir. Ana kelimeler: ĺnce-kabukler, Genel görelilik, Küresel Simetrik, Kararlı, ĺsrail sınır koşulları.
Master of Science in Physics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Physics, 2017. Co-Supervisor: Prof. Dr. Mustafa Halilsoy, Supervisor: Assoc. Prof. Dr. S. Habib Mazharimousavi.
Keywords: Relativity (Physics); Space and Time; Thin-shells; General relativity; Spherically symmetric; Stability; Israel junction conditions; Physics